Correlation of age and haematoma volume in patients with spontaneous lobar intracerebral haemorrhage. Issue 2 (28th July 2010) - Kuramatsu, Joji B; Sauer, Roland; Mauer, Christoph; Lücking, Hannes; Kloska, Stephan P; Kiphuth, Ines-Christine; Staykov, Dimitre; Köhrmann, Martin; Huttner, Hagen B
Abstract : Background: Lobar intracerebral haemorrhage (LH) is gaining importance in the ageing population, but there are only limited data regarding specific clinical characteristics and risk factors of older patients with LH. Methods: This retrospective analysis of patients with spontaneous supratentorial haemorrhage included 174 consecutive patients (78 LH and 96 deep ICH (DH)). Clinical data including the preadmission status, neuroradiological findings, initial presentation, treatment and outcome were evaluated using institutional databases, patients' medical charts and mailed questionnaires. Logistic regression analyses were calculated for initial parameters predisposing LH and for treatment and outcome parameters associated with LH. Results: Age-stratified volume analysis revealed increasing haematoma volumes for LH (≤70 years: 26.2 ml; 70–80 years: 37 ml; >80 years: 61.3 ml), whereas DH showed no relation between volume and age (≤70 years: 10.1 ml; 70–80 years: 23.2 ml; >80 years: 12.1 ml). DH patients had significantly higher HbA1c levels. Post-ICH seizures were more frequent after LH. Logistic regression analyses identified the parameters: age, haematoma volume and post-ICH seizures to be associated with LH, whereas intraventricular haemorrhage, extraventricular drainages and elevated HbA1c were related to DH. Conclusion: Haematoma volumes are substantially increasing in LH patients who are older than 70 years. Pathological HbA1c levels are significantly associated and predisposing for DH. These findings further support the ongoing debate of different disease entities for supratentorial ICH (ie, association of cerebral amyloid angiopathy and lobar ICH versus diabetes induced atherosclerosis in deep ICH). Future studies should focus on identifying specific pathological characteristics and risk factors for both bleeding sites to implement specific preventive measures, that is amyloid angiopathy modulating therapies for LH, and to avoid risk factors that are specific for each haemorrhage location.